A Cadaveric Study of the Communication Patterns Between the Buccal Trunks of the Facial Nerve and the Infraorbital Nerve in the Midface. Issue 1 (January 2016) - Tansatit, Tanvaa; Phanchart, Piyaporn; Chinnawong, Dawinee; Apinuntrum, Prawit; Phetudom, Thavorn; Sahraoui, Yasmina M.E.
Abstract : Abstract: Most nerve communications reported in the literature were found between the terminal branches. This study aimed to clarify and classify patterns of proximal communications between the buccal branches (BN) of the facial nerve and the infraorbital nerve (ION). The superficial musculoaponeurotic system protects any communication sites from conventional dissections. Based on this limitation, the soft tissues of each face were peeled off the facial skull and the facial turn-down flap specimens were dissected from the periosteal view. Dissection was performed in 40 hemifaces to classify the communications in the sublevator space. Communication site was measured from the ala of nose. A double communication was the most common type found in 62.5% of hemifaces. Triple and single communications existed in 25% and 10% of 40 hemiface specimens, respectively. One hemiface had no communication. The most common type of communication occurred between the lower trunk of the BN of the facial nerve and the lateral labial (fourth) branch of the ION (70% in 40 hemifaces). Communication site was deep to the levator labii superioris muscle at 16.2 mm from the nasal ala. Communications between the motor and the sensory nerves in the midface may be important to increase nerve endurance and to compensate functional loss from injury. Proximal communications between the main trunks of the facial nerve and the ION in the midface exist in every face. This implies some specific functions in normal individuals. Awareness of these nerves is essential in surgical procedure in the midface.